Pengaruh Likuiditas, Profitabilitas, Free Cash Flow Terhadap Kebijakan Hutang Dengan Kebijakan Dividen Sebagai Variabel Moderasi - Henly Sianturi; Darmae Nasir; Rini Oktavia; Lamria Simamora; Rapel Rapel; M. Ichsan Diarsyad (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
This study aims to analyze the effect of liquidity, profitability, free cash flow that can affect debt policy in Manufacturing Companies in the Goods and Consumer Sector listed on the Indonesia Stock Exchange in 2019-2022. This study uses a quantitative approach with data sources derived from secondary data in the form of financial statements. The population in this study is manufacturing companies in the goods and consumption sector with the number of samples used is as many as 22 companies with the purposive sampling method. Technical data analysis used simple linear analysis and Moderated Reggression Anaylisis (MRA) using SPSS tool version 25. The results of this study show that partially liquidity and profitability have a negative and significant effect on dividend policy, variable free cash flow has a positive and significant effect on debt policy. Dividend policy variables as variables cannot strengthen the relationship of liquidity to debt policy, profitability to debt policy, and free cash flow to debt policy.